1939
DOI: 10.1017/s0025315400014065
|View full text |Cite
|
Sign up to set email alerts
|

On a New Species of Gammarus (G. Trigrinus) from Droitwich District

Abstract: The new species of Gammarus here described was first noted in 1931 by Prof. H. Munro Fox, to whom I am indebted for the opportunity of examining it. He found it in abundance in the Droitwich district, living in the brackish waters of the River Salwarpe near the town, in the Canal, and in Wyken Slough near Coventry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…Within 1988-1991 three new benthic species: the spionid polychaete Marenzelleria viridis (Verrill, 1873), the gammarid crustacean Gammarus tigrinus Sexton, 1939, and another gammarid, Pontogammarus robustoides G. O. Sars, 1894 were found in samples collected in the inshore Pomeranian Bay, -374 382 378 Fig. 3: Records of Gammarus tigrinus in the river Odra estuary prior to 1997 (the animal's image after [45]).…”
Section: Recent Newcomersmentioning
confidence: 99%
See 2 more Smart Citations
“…Within 1988-1991 three new benthic species: the spionid polychaete Marenzelleria viridis (Verrill, 1873), the gammarid crustacean Gammarus tigrinus Sexton, 1939, and another gammarid, Pontogammarus robustoides G. O. Sars, 1894 were found in samples collected in the inshore Pomeranian Bay, -374 382 378 Fig. 3: Records of Gammarus tigrinus in the river Odra estuary prior to 1997 (the animal's image after [45]).…”
Section: Recent Newcomersmentioning
confidence: 99%
“…3: Records of Gammarus tigrinus in the river Odra estuary prior to 1997 (the animal's image after [45]). …”
Section: Recent Newcomersmentioning
confidence: 99%
See 1 more Smart Citation
“…G a m m a r u s tigrinus is a n indigenous species of mixohaline coastal w a t e r s b e t w e e n t h e St. Lawrence estuary a n d Florida (Steele & Steele 1972). Since 1939 it h a s b e e n recorded from t h e w e s t coast of England (Sexton 1939) in brackish a n d polluted waters. H y n e s (1955) concluded that it h a d b e e n introduced through t h e action of m a n .…”
Section: Field Data Laboratory Cyclementioning
confidence: 99%
“…Sexton, 1939). Uncommon, found mainly in low salinity areas near the mouth of the Apalachicola River.…”
Section: Key To the Males Of The Species In Thementioning
confidence: 99%